Catalytic Cooperativity, Nuclearity, and O2/H2O2 Specificity of Multi‐Copper(II) Complexes of Cyclen‐Tethered Cyclotriphosphazene Ligands in Aqueous Media. Issue 42 (3rd November 2017) - Wang, Le; Ye, Yong; Lykourinou, Vasiliki; Yang, Junliang; Angerhofer, Alexander; Zhao, Yufen; Ming, Li‐June
Abstract: Invited for the cover of this issue are the groups of Y. Ye from Zhengzhou University, China, A. Angerhofer from the University of Florida, USA, Y. Zhao from Xiamen University, China, and L.‐J. Ming from the University of South Florida, USA. The cover image shows the pathways for dinuclear catechol oxidation by Cu II complexes of cyclotriphosphazene derivatives with up to six metal‐binding sites. Abstract : This multi‐valent cyclic scaffold can hold active metal centers and recognition sites in close proximity… Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by Y. Ye, A. Angerhofer, Y. Zhao, L.‐J. Ming et al.